The Association between Neutrophil-to-Lymphocyte Ratio and Glycemic Control in Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis - Tiruneh Adane; Mulugeta Melku; Yilkal Belete Worku; Alebachew Fasil; Melak Aynalem; Amanuel Kelem; Solomon Getawa (Journal of Diabetes Research)
Background. Glycated hemoglobin (HbA1c) is a commonly used clinical marker to monitor the control of type 2 diabetes mellitus patients (T2DM). However, it is unable to identify the ongoing inflammatory changes in the body. These factors could be easily identified and monitored by the neutrophil-to-lymphocyte ratio (NLR). Therefore, this study is aimed at investigating the relationship between NLR and glycemic control in T2DM. Method. A comprehensive search of eligible studies was performed in various databases published until July 2021. A random effect model was used to estimate the standardized mean difference (SMD). A metaregression, subgroup, and sensitivity analysis were conducted to search for potential sources of heterogeneity. Result. A total of 13 studies were included in this study. Accordingly, the SMD of the NLR values between the poor and good glycemic control groups was 0.79 (95% CI, 0.46-1.12). Our study also showed that high NLR was significantly associated with poor glycemic control in T2DM patients (OR=1.50, 95% CI: 1.30-1.93). Conclusion. The results of this study suggest an association between high NLR values and an elevated HbA1C in T2DM patients. Therefore, NLR should be considered a marker of glycemic control in addition to HbA1c in T2DM patients.